(untitled) (Research, Society and Development, 2020)
The cashew residue is considered a raw material of paramount importance, in the agro-industrial system the full use of this residue is a goal that must be achieved. With that, the objective of this research was to develop and characterize cookies from the use of residue from the extraction of cashew juice from the cerrado. The cookies were made according to the adapted methodology, physical analyzes of diameter, thickness, average weight and volume were performed. The physical-chemical characterization of the samples was also carried out, determining: Moisture, Ashes, Lipids Proteins and Carbohydrates, as well as the determination of Salmonella and thermotolerant coliforms. recommended for all evaluated parameters.